Analysis Of Optimal Stock Portofolio In The Banking Sector Of Infobank15 On The Indonesia Stock Exchange For The Period 2023 - Shabana Ismi; Erna Retna Rahadjeng; Novi Puji Lestari (Manajemen Bisnis, 2024)
This study aims to identify stocks from companies included in the Infobank15 index on the Indonesia Stock Exchange (IDX) for the 2023 period that can form an optimal stock portfolio, along with the proportion of funds to be invested in each stock. Additionally, it calculates the expected return and risk of the resulting optimal stock portfolio. The population of this study consists of 15 stocks listed in the Infobank15 index. The sample used includes all 15 stocks, selected using a saturated sampling method. The analysis method is based on the Single Index Model. The analysis results indicate that 5 stocks form the optimal portfolio, namely PT Bank Mega Tbk (MEGA) at -13.60%, PT Bank Syariah Indonesia Tbk (BRIS) at 45.30%, PT Bank Mandiri (Persero) Tbk (BMRI) at 63.14%, PT Bank Negara Indonesia (Persero) Tbk (BBNI) at 2.39%, and PT Bank Central Asia Tbk (BBCA) at 2.77%. The expected return of the optimal portfolio is 2.4%, with a portfolio risk level of 0.025%. This study is expected to provide practical contributions to investors in making more accurate investment decisions and to enrich the literature on the application of the Single Index Model in the banking sector.